CMRepo End-to-End Automation (International Journal of Innovative Research in Computer Science & Technology, 2019)
Performance Automation is a technique  which helps in determining the performance of the system,  by determining various system parameters under  different workloads. This project aims at developing the  framework for determining the performance. It mainly  captures system level CPU and memory consumption  during any of the operations being performed. Whenever  any operation is done in CMRepo, the communication  takes place between client and CMRepo server. This  server hence communicates with relay, and relay to proxy.  Therefore, this framework also helps in capturing the  timestamps for each of the messages that are  communicated between client, server, relay and proxy.  CPU and Memory consumption, along with total time  taken to complete the whole operation help in determining  the performance of CMRepo. This project is done using  Python scripting and Unix commands. This paper  describes the designed framework that helps in  determining the overall performance of CMRepo. If the  determined performance is not matching with the  threshold values, it means that the operation is not  successful or if there’s any issue or bug within the  product. The data is captured at the idle condition of the  system as well as when the operation is performed. This  helps in giving clear picture of how the system is  performing at various conditions.
Keywords: IMS; CMRepo; CSCF; CPU; HSS; IMSMemory Performance